The winter war - Shirer, Priscilla, 1974-; Detwiler, Gina (Shirer, Priscilla, 1974- Prince warriors (Series), 2021)
Two years ago, the Prince Warriors lost one of their own, but now they must stand firm ... because death is coming once again. In this sequel, the Prince Warriors return to Ahoratos to find it bare and dangerous. The Winter War is upon them.--Adapted from back cover.